Agrarian legal regulation of agricultural activities of individuals: problem aspects - Saskevich, Veranika V. (Journal of the Belarusian State University. Law, 2023)
The article is devoted to the analysis of the legislation on breeding, veterinary activities, selection and seed production of agricultural plants, collective gardening. The trend of changes in legal regulation is revealed. This trend is expressed in the complication of the procedure for the implementation of certain types of agricultural activities, the exclusion of individuals from the circle of subjects of certain agrarian legal relations. The gaps in the regulation of the implementation of crop production and animal husbandry by citizens are identified. The conclusion about the need to create a special legal framework for the preservation and development of agricultural activities of individuals is substantiated.
Keywords: agricultural activities of individuals; legislation on breeding; subjects of seed production; veterinary and sanitary rules; collective gardening; agrarian law